A Research of Carbon Emissions Caused by Installation Faults in Air Conditioners Used in Heating Mode - Çalhan, Nurcan; Gürtürk, Mert (My University, 2025)
Air conditioners are among the most commonly used systems for fulfilling climate control requirements due to their dual capability to operate in both heating and cooling modes. When functioning in heating mode, these systems follow a cycle similar to that of a heat pump. However, failure to adhere to the installation guidelines provided by manufacturers, inadequate training of installation personnel, or user-driven installation modifications can result in increased energy consumption and suboptimal system performance. This study models improper installation practices of air conditioning systems and investigates their impacts on Life Cycle Climate Performance (LCCP) and annual energy consumption (AEC) during heating mode operation. In the experimental setup, airflow to the outdoor unit was progressively obstructed, and performance data were collected at various fan speed levels. Based on this data, LCCP and AEC analyses were conducted. Measurements were taken at multiple fan speeds corresponding to different degrees of airflow blockage. The scenario with unobstructed airflow was used as a reference point for comparison. When comparing the reference condition at 100 percent fan speed to the scenario with 93 percent airflow obstruction at the same fan speed, the LCCP value increased by 991.03 kilograms of CO2. In this obstructed condition, the AEC was found to be 26.89 percent higher than the reference case.
Keywords: Emissions; LCCP; heat pump; Air-conditioning